HAMBATAN GURU SD DALAM PENYUSUNAN SPP (SUBJECT SPECIFIC PEDAGOGY) SPKURIKULUM BARU DI SEKOLAH DASAR - Andri Anugrahana (Satya Widya, 2019)
The purpose of this study describes the obstacles of elementary school teachers in developing the Subject Specific Pedagogy (SSP) from new curriculum, the 2013 curriculum. This research is a descriptive exploratory study with a qualitative approach. Data were collected by questionnaire, interview, and focus group discussion. The data source is 40 elementary school teachers in Bantul Regency, DIY. Data analysis is done by finding and identifying teacher difficulties in preparing the SSP, then finding solutions to teacher problems. The results of this study are (1) 55% of teachers made preparations by determining the method in advance, 35% of teachers made preparations by determining SK and KD, and 10% of teachers chose to determine the approach. (2) The difficulty of teachers in preparing the SSP was 62% of teachers had difficulty in assessment, 32% of teachers had difficulty determining the method and 8% of teachers had other difficulties. (3) 62% of teachers answered the assessment became an obstacle in the preparation of the SSP, 32% of the teachers answered the method, and the other obstacle was 8%. The solutions made by the teacher to overcome the problem: find additional information, determine the syntax, choose a method, read book, search other source from the internet. Whereas in overcoming the assessment problems include the teacher compiling an assessment rubric according to the SSP guidelines, reading the assessment book.